Épocas de semeadura e populações de plantas para Cultivares de feijão-caupi no outono-inverno em Botucatu-SP - Matoso, Aline de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The cowpea [Vigna unguiculata (L.) Walp.] is becoming an option for farmers in different regions of the Brazil, for greater tolerance to water stress, short cycle, adaptation to soils with lower fertility and lower production cost. The cowpea crop has increased expansion, especially for growth the in second cropping season (out-ofseason) in the Midwest and Southeast regions of the country, and demand increase for domestic and foreign markets. However, there are not information and research on cowpea crop for the São Paulo state. The objective of this study was to evaluate the agronomic performance of semi-erect and semi-prostrate cowpea cultivars, at different sowing dates and plant populations, during the fall-winter, in the central region of the São Paulo state, Brazil. Two experiments were carried during the years 2011, 2012, and 2013, grown in a Typic Haplorthox (dystroferric Red Latosol) in Botucatu, São Paulo state. In the Experiment I, the randomized complete block design was used, in a split-plot arrangement, with four replications. In 2011, the plots consisted of four sowing dates: first half of and second half of March, and April. In 2012, of six sowing dates: first half of and second half of February, March, and April. And in 2013, of five sowing dates: first half of and second half of February, March, and first half of April. In the 2011, the subplots were composed by cowpea cultivars: BRS Cauamé, BRS Guariba, BRS Itaim, BRS Novaera, and BRS Tumucumaque. In 2012, by BRS Cauamé, BRS Guariba, BRS Novaera, BRS Potengi, and BRS Xiquexique. In 2013, has used the BRS Cauamé, BRS Guariba, BRS Novaera, BRS Potengi, and BRS Tumucumaque. The initial plant densities were 200.000 plants ha-1. In the Experiment II, the experimental design was a randomized complete blocks in a 2 x 5 factorial scheme, with four replications. The treatments of the factorial consisted of the ...

O feijão-caupi [Vigna unguiculata L. Walp.] está se tornando uma opção para os produtores de diferentes regiões do Brasil, pela maior tolerância ao estresse hídrico, ciclo rápido, adaptação a solos de menor fertilidade e menor custo de produção. A cultura apresenta crescente expansão, em especial para o cultivo na segunda safra (safrinha), nas regiões Centro-Oeste e Sudeste do país, e aumento da demanda pelos mercados interno e externo. Porém, são praticamente inexistentes informações sobre esta cultura no estado de São Paulo. Objetivou-se com este trabalho avaliar o desempenho produtivo de cultivares de feijão-caupi, de porte semiereto e semiprostrado, em diferentes épocas de semeadura e populações de plantas, no período de outono-inverno, na região central do estado de São Paulo. Foram conduzidos dois experimentos, durante os anos de 2011, 2012 e 2013, em um Latossolo Vermelho distroférrico, em Botucatu-SP. No Experimento I, o delineamento foi o de blocos casualizados, em esquema de parcela subdivididas e quatro repetições. Em 2011, as parcelas foram compostas por quatro épocas de semeadura: 1a quinzena de março; 2a quinzena de março; 1a quinzena de abril e 2a quinzena de abril. Em 2012, por seis épocas: 1a quinzena de fevereiro; 2a quinzena de fevereiro; 1a quinzena de março; 2a quinzena de março; 1a quinzena de abril e 2a quinzena de abril. E no ano de 2013, por cinco épocas: 1a quinzena de fevereiro; 2a quinzena de fevereiro; 1a quinzena de março; 2a quinzena de março e 1a quinzena de abril. Em 2011, as subparcelas foram compostas pelas cultivares: BRS Cauamé, BRS Guariba, BRS Itaim, BRS Novaera e BRS Tumucumaque. Em 2012, por BRS Cauamé, BRS Guariba, BRS Novaera, BRS Potengi e BRS Xiquexique. Em 2013, utilizou-se a BRS Cauamé, BRS Guariba, BRS Novaera, BRS Potengi e BRS Tumucumaque. Foi utilizada a população ...
Sowing times and plant population to cowpea cultivars grown in fall-winter in Botucatu-sp
Keywords: Feijão-de-corda - influencia do clima; Semeadura - Fatores climaticos; Feijão - Cultivo; Beans